2010
DOI: 10.1164/rccm.200904-0627oc
|View full text |Cite
|
Sign up to set email alerts
|

Dual Inhibition of Cathepsin G and Chymase Is Effective in Animal Models of Pulmonary Inflammation

Abstract: The preclinical antiinflammatory effects of RWJ-355871 in these animal models of inflammation indicate that this dual inhibitor may have therapeutic utility for treating airway inflammatory diseases involving mechanisms that depend on Cat G and/or chymase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 49 publications
2
44
0
Order By: Relevance
“…The importance of proteinases in the development of AHR and airway inflammation has been shown [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of proteinases in the development of AHR and airway inflammation has been shown [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…The DCCI used in this study was shown to selectively inhibit Cat.G and chymase in vitro, with little effect on several other serine proteases such as thrombin, factor Xa, trypsin, tryptase, proteinase 3, and elastase [6]. DCCI has been shown to markedly reduce neutrophil influx and nitric oxide levels associated with lipopolysaccharide-induced lung inflammation [23]. In the present study, we describe how DCCI administration to mice subjected to IR injury resulted in reduced myocardial Cat.G and chymase activity and pathologic remodeling associated with IR.…”
Section: Introductionmentioning
confidence: 91%
“…Whether the potential safety advantages associated with high selectivity occur at the expense of efficacy is as yet unknown. Pr3 and catG, the two other granule-associated serine proteases in neutrophils, individually have the potential to contribute to human COPD by multiple mechanisms often with significant overlap to NE (Maryanoff et al, 2010), but in contrast to NE, their role in human COPD or the relevant smoke-driven animal models has yet to be demonstrated.…”
Section: Downloaded Frommentioning
confidence: 99%